Identification of potential agronomic lines among Nigerian pigeonpea (Cajanus cajan L. Millsp.) accessions for crop improvement - Amusa, Oluwafemi; Okpanachi, Fidelis Etuh; Onyeka, Samuel Chimezie; Damilola, Jonathan Samson; Olatunji, Elizabeth Oluwaseun; Ogunkanmi, Liasu Adebayo; Oboh, Bolanle Olufunmilayo (Revista de Ciencias Agrícolas, 2022)
Pigeonpea (Cajanus cajan (L.) Millsp.) is a grain legume crop from the tropics and subtropics cultivated for its highly nutritious seeds. Relatively low yields have been observed among African accession with little information on germplasm performance. Therefore, it is needed to identify resilient germplasm, varieties or accessions to improve agronomic performance. This study assessed the morphological variability among selected accessions of Nigerian pigeonpea to identify potential lines for agronomic improvement. A total of 52 Nigerian pigeonpea accessions were evaluated using 10 qualitative and 13 quantitative morphological traits. They were planted using a completely randomised design. Yield performance, trait correlation, principal component (PC), and cluster analysis were used to identify potential breeding lines. The study revealed a wide variability among pigeonpea accessions with both qualitative and quantitative traits. The 52 pigeonpeas were clustered into three major groups. Four principal components with eigenvalue > 1 accounted for 68.95% of the total variation observed. The first PC accounted for 30.13% with yield components, which include days to 50% flowering, plant height, days to 50% maturity, and vigour at 50% flowering as major contributors. These traits also showed strong significant correlations between themselves. Hence, they can be improved simultaneously. The study identified several potential accessions based on performance that can be selected for multilocational evaluations and crop improvement.